(3TQM GdcGajIs - (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3HOQGdOjf eMehO Hf CMeO GdYjfj s)
(3ChdgG (B:s
(3hcPG Jbhd(B: (3cCf JSYI JcedJgG YTQI Cj UjQJgG YTQI cGedI bGd GdeUfa QMeg Gddg(B: (3djS bhdfG GdehUhd s
(3BNQgG (B:s
(3HNdGa GdJfhjf dchf GdJfhjf dGReI acCfgG KGHJI CjVkG eY YQhV GdMPa hgPG BNQ TQM GdebOeI, s
(3HgG fXGe GdJYbjHIs
(3eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs